Examination of Normative Legal Acts and its Role in Improving Legal Regulation - Prekeeva Tillaxan Markabaevna (Zien Journals, 2022)
This article analyzes the problems of examination of a normative legal act, ways to improve the effectiveness of legislation.
Keywords: Legal acts; regulation; examination; lawyer